SPEECH ETIQUETTE AND LANGUAGE NORMS IN COMMUNICATION - Qaypova, B. (SCIENCE and SOCIETY, 2025)
This article aims to analyze norms of speech etiquette in English and Karakalpak, focusing on how politeness strategies reflect broader societal values and facilitate intercultural communication. Greetings, forms of address, requests, apologies, and expressions of gratitude are compared and the study reveals how each language encodes respect, hierarchy, and social distance through different pragmatic means. These findings suggest that speech etiquette serves not only as a linguistic phenomenon but as a bridge between cultures, enhancing mutual understanding when used appropriately.